A new method for estimating the pattern speed of spiral structure in the Milky Way. Issue 3 (31st March 2015) - Junqueira, T. C.; Chiappini, C.; Lépine, J. R. D.; Minchev, I.; Santiago, B. X.
Abstract : In the last few decades, many efforts have been made to understand the effect of spiral arms on the gas and stellar dynamics in the Milky Way disc. One of the fundamental parameters of the spiral structure is its angular velocity, or pattern speed Ωp, which determines the location of resonances in the disc and the spirals' radial extent. The most direct method for estimating the pattern speed relies on backward integration techniques, trying to locate the stellar birthplace of open clusters. Here, we propose a new method based on the interaction between the spiral arms and the stars in the disc. Using a sample of around 500 open clusters from the New Catalogue of Optically Visible Open Clusters and Candidates, and a sample of 500 giant stars observed by Apache Point Observatory Galactic Evolution Experiment, we find Ωp = 23.0 ± 0.5 km s −1 kpc −1, for a local standard of rest rotation V 0 = 220 km s −1 and solar radius R 0 = 8.0 kpc. Exploring a range in V 0 and R 0 within the acceptable values, 200–240 km s −1 and 7.5–8.5 kpc, respectively, results only in a small change in our estimate of Ωp, that is within the error. Our result is in close agreement with a number of studies which suggest values in the range 20–25 km s −1 kpc −1 . An advantage of our method is that we do not need knowledge of the stellar age, unlike in the case of the birthplace method, which allows us to use data from large Galactic surveys. The precision of our method will be improved once larger samples of disc stars with spectroscopic information will become available thanks to future surveys such as 4MOST.